THE ROLE OF SANTRI PRESS AS MEDIA INFORMATION AND EDUCATION IN PESANTREN DARUL HUDA MAYAK - Taufik, Ahmad (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Darul Huda Mayak Ponorogo Islamic Boarding School applies regulations in limiting the use of communication technology for students. To overcome students who lack updated information, Darul Huda uses the student press agency as a provider of information about cottage activities, and dissemination of information outside the cottage. The purpose of this study is to see the role of the Santri Press Institute in providing information and education needs in Ponpes Darul Huda Mayak and analyze how the effect of the Santri Press Institute as a medium of information and education. The research approach used by researchers is Case Studies which is a qualitative descriptive research method. The result of his research is the role of the Santri Press Institute in providing information in Pondok Mayak through the media of wall magazines and cottage information boards, while educational media through learning journalism courses and can play a role in filtering information news from outside the cottage about things that are appropriate to be disseminated or not. The effect of the Santri Press Institute in using mading media and information boards causes students to know about events outside the cottage, this includes the cognitive effects of the media. Santri also participates in journalism courses, thus making the influence included in affective effects. The existence of journalistic work from the Santri Press Institute is able to make students feel the conative effect that is able to change their attitude into right and good behavior.